Goma arábica e eugenol na angiogênese inflamatória em novo modelo de inóculo de sílica subcutâneo em ratas wistar - Dutra, Barbara de Araujo Lima (2021)
The process of angiogenesis is defined as the formation of new blood vessels by a process of endothelial sprouts germinating from preexisting capillaries. This event is related to several physiological processes such as morphogenesis and wound healing. The objective of this work was to evaluate the effects of gum arabic and eugenol on inflammatory angiogenesis in a new model of subcutaneous silica inoculum through histological analysis of slides stained with hematoxylin-eosin and through immunohistochemistry with CD 31. Ninety and six Wistar rats were distributed in 16 groups containing 06 animals each. The substances administered via gavage were: distilled water, gum arabic PA (500 mg/100 g of weight) and eugenol (10 mg/100 g of weight). Control groups (I, II, III, IV, IX, X, XI and XII) received an inoculum of 0.2 mL of sterile distilled water subcutaneously. The experimental groups (V, VI, VII, VIII and XIII, XIV, XV and XVI) were submitted to the inoculum of 0.2 mL of silica solution (50 mg/mL) subcutaneously. Groups I and V received distilled water for 7 days and groups IX and XIII received it for 14 days; groups II and VI received gum arabic and eugenol for 7 days, and groups X and XIV for 14 days; groups III and VII received gum arabic for 7 days, and groups XI and XV for 14 days; groups IV and VIII received eugenol for 7 days, and groups VIII and XVI received it for 14 days. Slides were evaluated at 400x magnification in a total of 5 fields. Even with different amounts of treatment days, there was no difference between the histological findings between the groups. The groups that received gum arabic showed a decrease in vascular density, both those treated for 7 days (0.09 μm² ± 0.02) and those treated for 14 days (0.08 μm² ± 0.03), but it did not occur in a similar way. clinically significant. In animals that received only eugenol for 7 days, there was a reduction in vascular density (angiogenesis), however, it was not statistically significant (0.08 μm² ± 0.03). In the groups treated for 14 days, there was a statistically significant stimulus to angiogenesis (0.14 μm² ± 0.02). The novel experimental model of silica inoculum on the back of Wistar rats was successfully developed. Eugenol inhibited inflammatory angiogenesis in this model, when administered for 7 days, and stimulated angiogenesis in the groups treated for 14 days.